2012
DOI: 10.1089/ars.2011.3994
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Pyruvate Induces Heme Oxygenase-1 Through p38 Mitogen-Activated Protein Kinase Activation by Depletion of Glutathione in RAW 264.7 Cells and Improves Survival in Septic Animals

Abstract: Aims: We investigated the molecular mechanism by which ethyl pyruvate (EP) induces heme oxygenase-1 (HO-1) in RAW 264.7 cells and its effect on survival rate in cecal ligation and puncture (CLP)-induced wild-type (WT) and HO-1 knockout (HO-1 -/ -) septic mice. Results: EP induced HO-1 in a dose-and time-dependent manner, which was mediated through p38 mitogen-activated protein kinase (MAPK) and NF-E2-related factor 2 (Nrf2) signaling cascade in RAW 264.7 cells. EP significantly inhibited the lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…Additionally, previously published studies demonstrated that p38 MAPK triggered activation of NRF2 resulting in induction of the Ho-1 gene (Jang et al, 2012;Park et al, 2013), suggesting that WZ pretreatment seemed to activate NRF2-ARE pathway via p38 MAPK. ALR is identified to promote liver regeneration after partial hepatectomy and to augment hepatocyte proliferation (Polimeno et al, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, previously published studies demonstrated that p38 MAPK triggered activation of NRF2 resulting in induction of the Ho-1 gene (Jang et al, 2012;Park et al, 2013), suggesting that WZ pretreatment seemed to activate NRF2-ARE pathway via p38 MAPK. ALR is identified to promote liver regeneration after partial hepatectomy and to augment hepatocyte proliferation (Polimeno et al, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…2,25 The anti-inflammatory activities of pyruvate have been associated with i) the inhibition of cellular adhesion to the endothelium, 3 ii) the inhibition of NADPH-oxidase in kidney lesion, 2 iii) the association between the up-regulation of HO-1 and the inhibition of nitric oxide synthase expression associated with high-mobility group box 1 (HMGB-1) release in RAW 264.7 cells, 7 and iv) the down-regulation of oxidative stress and HMGB-1 expression during lung injury in C57BL/mice. 25 The results obtained in the present study demonstrate the effects of pyruvate on ROS generation during phagocytosis or toll-like receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism through the pentose phosphate pathway provides NADPH to maintain glutathione in the reduced state. 27,28 Jang et al 7 demonstrated that glutathione ethyl ester (GSH-Et), SB203580 (p38 MAPK inhibitor), siHO-1, or p38-siRNA transfection abolished the anti-inflammatory effect of ethyl pyruvate. Kamata et al, 29 showed…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-HMGB1 antibodies and HMGB1 inhibitors significantly improve survival in septic animals, suggesting that HMGB1 is a possible therapeutic target in sepsis (Barnay-Verdier et al, 2011;Sama et al, 2004). Heme oxygenase-1 (HO-1), a stress-responsive protein induced by stimulants (inflammatory cytokines, heat shock, heavy metals, and oxidants) (Jang et al, 2012;Tsoyi et al, 2009) decreases circulating HMGB1 levels in animal models of sepsis and improves patient survival, demonstrating its therapeutic potential in inflammatory disorders . In addition, it is well known that the inducers of HO-1 expression inhibits the expression of the inflammatory genes (cyclooxygenase-2 and inducible nitric oxide synthase), and subsequently decreases PGE 2 and NO production (Oh et al, 2006;Suh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%